Analysis of Determinants of Interest in Paying Professional Zakat of Civil Servants at Madrasah Aliyah Negeri 2 Padangisidimpuan with Awareness as an Intervening Variable Intervening - Nasrun Efendy; Ibrahim Siregar; Rukiah Rukiah (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
This research is motivated by a phenomenon where in several previous studies that the religiosity of interest and awareness of civil servants in paying zakat is still quite low where when there is an appeal from the Padang Sidimpuan Ministry of Religion to distribute zakat to the profession, the acquisition of zakat can reach Rp. 4,600,000 s.d. Rp. 4,800,000. But at this time, in the absence of direct deductions, the zakat received is only around Rp. 1,000,000 to Rp. 2,000,000. So the purpose of this research is to find out how religiosity, income and education actually influence the intention to pay zakat through awareness. This research is a quantitative study with a total sample of 45 samples. The data collection instrument was carried out by conducting structured interviews with each respondent by providing a questionnaire to fill out. Data analysis used the outer model test, the inner model and tested the hypothesis on each of the variables studied. Based on the research results, it is known that there is an influence between religiosity on awareness (3.122 > 1.96) and p-value < 0.05 (0.003 < 0.05). There is no effect between income on awareness (0.747 < 1.96) and p-value > 0.05 (0.459 > 0.05). There is an influence between education on awareness (2.192 > 1.96) and p-value < 0.05 (0.034 > 0.05). There is an influence between religiosity on intention to pay zakat (6.167 > 1.96) and p-value < 0.05 (0.000 < 0.05). There is no effect between education on intention to pay zakat (1.922 < 1.96) and p-value > 0.05 (0.214 > 0.05). There is an influence between awareness of interest in paying zakat (2.685 > 1.96) and p-value < 0.05 (0.010 < 0.05). There is no influence between religiosity on intention to pay zakat through awareness (1.732 < 1.96) and p-value > 0.05 (0.090 > 0.05). There is no influence between income on intention to pay zakat through awareness (0.651 < 1.96) and p-value > 0.05 (0.519 > 0.05). There is no influence between education on intention to pay zakat through awareness (1.922 > 1.96) and p-value > 0.05 (0.214 > 0.05) at Madrasah Aliyah Negeri 2 Padangsidimpuan.